A survey of crystal structures and biological activities of platinum group metal complexes containing N-acylthiourea ligands. (2nd October 2020) - Lapasam, Agreeda; Kollipara, Mohan Rao
Abstract: N -Acyl-thioureas are important compounds in the field of organic synthesis and medicinal chemistry. Research interest in these compounds has grown recently because coordination to metal ions enhances their application especially in view of medicinal studies. These thiourea derivatives possess rich coordination chemistry and the coordination behavior of these derivatives alters upon reaction with different metals. Such ligands generally coordinate to Pt(II) and Pd(II) ions in a bidentate S, O manner and often coordinate to Ru(II), Rh(III) and Ir(III) centers through the S donor atom. We isolated some complexes of these ligands by reaction with sodium azide which coordinates to Ru(II), Rh(III), and Ir(III) in a bidentate S, N fashion. The deprotonated thiourea nitrogen atom resulted in the formation of strained 4-membered ring structures around the metal center. Biological application of N -acyl thiourea derivatives and their platinum group metal complexes are further discussed. Studies has shown that these compounds can be used as drugs to treat several human diseases like microbial infections, tuberculosis, carcinomas, malaria, leishmaniasis, urease inhibitors and anti-inflammatory. This review intends to summarize the recent advancement in the chemistry of N -acyl-thioureas and highlight some perspectives in the synthesis, versatile coordination behavior to ruthenium, rhodium, iridium, platinum and palladium, and their metal complexes in biological applications. Graphical Abstract: